2006
DOI: 10.1002/bem.20285
|View full text |Cite
|
Sign up to set email alerts
|

Low‐power millimeter wave radiations do not alter stress‐sensitive gene expression of chaperone proteins

Abstract: This article reports experimental results on the influence of low-power millimeter wave (MMW) radiation at 60 GHz on a set of stress-sensitive gene expression of molecular chaperones, namely clusterin (CLU) and HSP70, in a human brain cell line. Selection of the exposure frequency is determined by its near-future applications for the new broadband civil wireless communication systems including wireless local area networks (WLAN) for domestic and professional uses. Frequencies around 60 GHz are strongly attenua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…Therefore, the energy of a millimeter wave can be absorbed by the organism through resonance. In turn, the energy can interfere with signal transduction and affect metabolism (8)(9)(10). It has been shown that a millimeter wave can evoke multiple biological effects (11,12) and is useful in the treatment of various types of diseases including cancers, such as hepatic cellular cancer patient (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the energy of a millimeter wave can be absorbed by the organism through resonance. In turn, the energy can interfere with signal transduction and affect metabolism (8)(9)(10). It has been shown that a millimeter wave can evoke multiple biological effects (11,12) and is useful in the treatment of various types of diseases including cancers, such as hepatic cellular cancer patient (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of the millimeter wave is in the same range of the frequency (0.5x10 10 -3x10 12 ) of coherent oscillation produced by biological organisms during metabolism. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the energy of a millimeter wave can be absorbed by the organism through resonance. In turn, the (11)(12)(13). Our previous study showed that millimeter wave treatment induced the direct differentiation of mesenchymal stem cells (MSCs) to chondrocytes by upregulating the mRNAs of Cbfa1 and Sox9 and ultimately the levels of glycosaminoglycan and type II collagen.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the energy of MW can be absorbed by the organism through resonance. In turn, the energy may interfere with signal transduction and affect metabolism (10)(11)(12)(13). MW has been shown to evoke multiple biological effects and is beneficial in the treatment of OA.…”
Section: Introductionmentioning
confidence: 99%